2001
DOI: 10.1038/ng1001-223
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the 5q31 cytokine gene cluster confers susceptibility to Crohn disease

Abstract: Linkage disequilibrium (LD) mapping provides a powerful method for fine-structure localization of rare disease genes, but has not yet been widely applied to common disease. We sought to design a systematic approach for LD mapping and apply it to the localization of a gene (IBD5) conferring susceptibility to Crohn disease. The key issues are: (i) to detect a significant LD signal (ii) to rigorously bound the critical region and (iii) to identify the causal genetic variant within this region. We previously mappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
489
2
6

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 703 publications
(511 citation statements)
references
References 14 publications
14
489
2
6
Order By: Relevance
“…These studies included diverse populations and originated from Canada [6,13,14], the UK [15][16][17][18], Germany [19], New Zealand [20], Spain [21], Italy [22,23], Belgium [24], Greece [25], Sweden [26] and Japan [27,28]. One Japanese and another Hungarian study with a small number of subjects found no association between OCTN 1&2 transporter polymorphisms and CD [28,29]; thus there could be ethnic differences in IBD5 locus mutations and propensity for Crohn's disease [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies included diverse populations and originated from Canada [6,13,14], the UK [15][16][17][18], Germany [19], New Zealand [20], Spain [21], Italy [22,23], Belgium [24], Greece [25], Sweden [26] and Japan [27,28]. One Japanese and another Hungarian study with a small number of subjects found no association between OCTN 1&2 transporter polymorphisms and CD [28,29]; thus there could be ethnic differences in IBD5 locus mutations and propensity for Crohn's disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…After the initial association study of IBD5 locus with CD by Rioux et al in 2001 [13], 19 large scale independent studies involving more than 5000 patients with CD and equal numbers of controls have confirmed this association with an odds ratio varying from 1.1 to 20. Our metaanalysis of the combined data from 12 of these studies including 3420 patients and an equal number of matched controls, indicated that the odds of acquiring CD when the risk haplotype was present ranged from 1.5 to 2.0 (Table 1).…”
Section: Ibd5 Locus Mutations In Octn1 and Octn2 Carnitine Transportementioning
confidence: 94%
“…5,6 Genome-wide linkage studies have identified evidence of linkage of this region with bronchial asthma [7][8][9] and other inflammatory disease such as Crohn's disease. 10 Despite numerous genetic-association studies, [11][12][13][14][15][16][17] the involvement of the IL-13/ IL-4 locus in susceptibility to allergic disease is unclear. Since the two loci are so closely linked and similar in function, it is not clear as to which might be responsible for the observed association.…”
Section: Introductionmentioning
confidence: 99%
“…20 In addition, this region on chromosome 5 coincides with the IBD5 region that showed significant evidence of linkage and association with Crohn's disease, an inflammatory bowel disease closely associated with Mycobacterium paratuberculosis. 21 It is interesting to note that the IBD5 haplotype is distributed differently in Asian and European populations, and that the IBD5 risk haplotype in Europeans is very rare in Asians. 22 Although candidate genes including IL4 23 and CD14 24,25 have been studied in this particular region, roles of these genes in tuberculosis remain inconclusive.…”
Section: Discussionmentioning
confidence: 99%